Cardiovascular Metrics Associated With Prevention of Aging-Related Parkinsonian Signs Following Exercise Intervention in Sedentary Older Rats - Kasanga, Ella A.; Little, Joel; McInnis, Tamara R.; Bugnariu, Nicoleta; Cunningham, J. Thomas; Salvatore, Michael F. (Frontiers in Aging Neuroscience, 2021)
Preservation of motor capabilities is vital to maintain independent daily living throughout the lifespan and may mitigate aging-related parkinsonism, a progressive and prevalent motor impairment. Physically active lifestyles can mitigate aging-related motor impairment. However, the metrics of physical activity necessary for mitigating parkinsonian signs are not established. Consistent moderate intensity (~10 m/min) treadmill exercise can reverse aging-related parkinsonian signs by 20 weeks in a two weeks on-, two weeks off, regimen in previously sedentary advanced middle age rats. Here we initiated treadmill exercise in sedentary 18 month old male rats to address two questions; 1) if a rest period not longer than one week off-exercise, with 15 exercise sessions per month, could attenuate parkinsonian signs within 20 weeks after exercise initiation, and 2) determine how heart rate (HR) and mean arterial pressure (MAP) were affected in association with possible exercise-related prevention of parkinsonian signs. The treadmill exercise intensity and frequency attenuated aging-related parkinsonian signs by eight weeks and was maintained out to 23 months old. The exercise regimen increased HR by 25% above baseline, and gradually reduced baseline MAP. Together, these studies indicate that a practicable frequency and intensity of exercise affects reduces parkinsonian sign severity commensurate with a modest increase in HR after exercise. These cardiovascular changes provide a baseline of metrics, easily measured in humans, for predictive validity that a practicable exercise intensity and schedule can be initiated in previously sedentary older adults to delay onset of aging-related parkinsonian signs.